The machinery of autobiography in selected political autobiographies from Zimbabwe - Nyanda, Josiah (My University, 2016)
The study explores the ways in which the self and other are constructed and represented in a wide range of Zimbabwean political autobiographical narratives from 1972 to 2011. In particular, it focuses on the machinery of autobiography and the various narrative strategies deployed by autobiographers of different races, gender, ethnic origins and political persuasions to construct the self and other. It also considers how these representations of the self and other, combined with the narrative strategies used, bear upon the history and politics of Zimbabwe. The argument is advanced that through strategic and careful deployment of narrative in transforming lives lived to lives told, the selected narratives not only reconstruct the self and other but also narrate the history and politics of the nation. Therefore, the deployment of different narrative strategies, which include the uses of: authentication, patronage of authorship, historical recurrence and narcissistic rage, erasure, palimpsest and collaborative voices, and hauntology has resulted in the emergence of a seemingly minor genre into a competing narrative that is threatening to take over the place of hegemonic grand narratives and histories of Zimbabwe. These have all along been largely nativist and based on racial, ethnic and patriarchal prejudices, especially in the manner in which they narrated the political history of Zimbabwe. The study thus argues that the machinery of autobiographies has been deployed as political weaponry to present bleached images of the self and other. This situates Zimbabwe’s political autobiographies as literary and political projects and archives that narrate the nation through the story of the self and other.
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy Johannesburg, June 2016
Keywords: Autobiography in literature; Autobiography; Politics and literature--Zimbabwe; Zimbabwe--In literature